2020
DOI: 10.3390/foods9010051
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Advertising Coming to Its Senses: The Effectiveness of Sensory Appeals in Healthy Food Advertising

Abstract: With increasing obesity rates and the daily overload of unhealthy food appeals, an important objective for advertising today is to promote healthy food consumption. According to previous research, sensory food advertisements referring to multiple senses-a combination of visual (sight), tactile (touch) and olfactory (smell) cues-evoke more positive sensory thoughts and, therefore, higher taste perceptions than advertisements referring to a single sense (e.g., only taste cues). However, this research only focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…Further, we contribute to advertising research on healthy food promotion, by investigating a commonly used visual cue to display food. Previous research has shown that visual elements in food pictures can affect consumers’ responses to healthy and unhealthy food differently [ 6 , 34 ]. However, we find that implied motion does not impact consumer perceptions of healthy and unhealthy food products differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we contribute to advertising research on healthy food promotion, by investigating a commonly used visual cue to display food. Previous research has shown that visual elements in food pictures can affect consumers’ responses to healthy and unhealthy food differently [ 6 , 34 ]. However, we find that implied motion does not impact consumer perceptions of healthy and unhealthy food products differently.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when food pictures are shot from a top perspective (vs. a diner’s eye perspective), consumers choose less unhealthy food [ 6 ]. On the other hand, promoting healthy food in sensory advertising is found to be the most effective by visually presenting single-sense (vs. multiple-sense) elements [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, products perceived as healthy (virtue) do not benefit from the same promotion strategies as more tempting products (vice). In fact, a recent study showed that evoking a multisensory experience of the food (e.g., taste, smell, enjoyment), a wide strategy used to promote vice foods [19] compared to a single-sense ad slogan (mentioning taste only), resulted in more negative thoughts when a healthy food (cherry tomatoes) was used [20]. Understanding how these simulations operate, also with virtue foods, is relevant to promote healthier choices at an individual level but it also contributes to a better understanding of how these foods behave in people's minds, which could help companies to adapt their promotion strategies according to their product categories.…”
Section: Introductionmentioning
confidence: 99%
“…Vision . In the food industry, it is commonly suggested that, for unhealthy foods, ads stimulating multisensory channels “work best” ( Elder and Krishna, 2010 ), while single-sense ads are successful to advertise healthy foods ( Roose and Mulier, 2020 ), and that manipulation of the visual field (e.g., background/packaging/colour, dark/pale) can lead to differences in expected flavour and boost sales indirectly ( Carvalho et al, 2017 ; Spence, 2019 ). Colour, shape, size, and shining transparency, reflections, and special textures can play a role in costumers’ decision-making processes ( Manenti, 2013 ).…”
Section: The Helsinki Declaration Of Experimentation With Human Subjectsmentioning
confidence: 99%